Phase I Cardiovascular Rehabilitation, Risk Stratification, and Length of Hospitalization in Post-Percutaneous Coronary Intervention (PCI) Patients - Muhammad Sukri Tanjung; Dudut Tanjung; Nur Asnah Sitohang; Dedi Ardinata (Poltekkes Kemenkes Tanjung Karang, 2024)
Percutaneous Coronary Intervention (PCI) is one of the most effective actions for patients with Acute Coronary Syndrome (ACS), which can improve prognosis and minimize hospitalization time. To optimize medical therapy programs, PCI must be complemented with further preventive measures, such as cardiovascular rehabilitation, including lifestyle modification and risk stratification. This study aims to analyze the relationship between phase I cardiovascular rehabilitation, risk stratification, and length of hospitalization in post-PCI patients. The study design was a retrospective cohort sourced from electronic medical record data. Respondents were divided into groups: those exposed and those not exposed to phase I cardiovascular rehabilitation. Risk stratification and length of hospitalization were studied as study outcomes. Among 201 patients who were followed up during hospitalization, high-risk stratification was more in the unexposed group: exposed group (92.2%: 90.8%; RR 0.85, 95%CI 0.340-2.104). Length of hospitalization ≥3 days was more in the unexposed group: exposed group (63.1%: 59.2%; RR 0.904 95%CI (0.639-1.279). Length of hospitalization ≥3 days was more in the high stratification group: low stratification (63.6%: 35.3%; RR 0.555 95%CI (0.289-1.066). Phase I cardiovascular rehabilitation was not associated with risk stratification and length of hospitalization. Patient risk stratification was related to the length of hospitalization of post-PCI patients. Phase I cardiovascular rehabilitation is an integral part of medical therapy that can reduce adverse events in post-PCI patients.